1998
DOI: 10.1086/514247
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiosis in Northeastern Brazilian Children: Association with Increased Diarrhea Morbidity

Abstract: To evaluate the impact of Cryptosporidium infection on diarrheal disease burden and nutrition status, a nested case-control study was done among children who were followed from birth in Fortaleza, Brazil. The diarrhea history and growth records of 43 children with a symptomatic diarrhea episode of cryptosporidiosis (case-children) were compared with those of 43 age-matched controls with no history of cryptosporidiosis. After Cryptosporidium infection, case-children < or = 1 year old experienced an excessive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
63
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 30 publications
5
63
1
3
Order By: Relevance
“…Diarrhea caused by these parasites in early childhood has been associated with subsequent cognitive function deficits and growth faltering and stunting, and the risk of stunting increases with the number of episodes per year. [1][2][3][4][5][6] A study from Peru found that symptomatic and asymptomatic cryptosporidiosis in children were associated with growth faltering after an infection but recovery was slower in children with symptomatic infection. 7 In India, several studies have reported Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea caused by these parasites in early childhood has been associated with subsequent cognitive function deficits and growth faltering and stunting, and the risk of stunting increases with the number of episodes per year. [1][2][3][4][5][6] A study from Peru found that symptomatic and asymptomatic cryptosporidiosis in children were associated with growth faltering after an infection but recovery was slower in children with symptomatic infection. 7 In India, several studies have reported Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In immunocompetent individuals, Cryptosporidium infection causes watery diarrhea, often continuing beyond 10 days from the onset [7]. Cryptosporidium is a major cause of diarrhea in children in developing countries and is associated with stunting, irreversibly impaired cognitive development, and decreased fitness [9][10][11]. With improved diagnostic data from the Global Enteric Multicenter Study (GEMS), Cryptosporidium infections are now linked to approximately 25% of moderate-to-severe diarrheal episodes in children aged <2 years in resource-limited countries, second only to rotavirus [3].…”
mentioning
confidence: 99%
“…However, in patients with defects in cellular immune responses (e.g., AIDS, malnutrition, or defects in the CD40-CD154 system), Cryptosporidium frequently causes persistent or chronic diarrhea and may also involve the biliary tract (40). In malnourished children, persistent diarrhea is associated with increased susceptibility to recurrent diarrheal episodes, which can lead to death or chronic nutritional and cognitive sequelae (1,9,33). Thus, the host immune response plays a critical role in the control of human cryptosporidiosis.…”
mentioning
confidence: 99%